A profitable implementation of collaborative robots - A safe and affordable way of increasing production rate and quality - Bredvad-Jensen, Johan; Johansson, Jakob (My University, 2023)
At Volvo Powertrain in Skövde combustion engine cylinder heads are casted at foundry 2. Most of the manufacturing of their products is fully automated, but the assembly of the sand cores prior to casting for the D6 and D4 cylinder heads is manual, since they are produced in smaller quantities. At the current workstation the manual assembly creates a bottleneck, due to problems with the production and error rates. Volvo Powertrain therefore wants a study performed about the possibility of using collaborative robots for the gluing of the sand cores. To find a suitable concept for a new workstation a requirement specification was created. With idea generation methods, concepts were created and later evaluated using decisions matrices until a final concept remained. In unison with the decision matrices. A simplified risk assessment was performed and data from recordings of the current production was acquired. The data acquired was then statistically evaluated with the three-point method. This was then used in the visualisation. After the visualisation a simplified ergonomic and economic evaluation was performed. The final concept consisted of two collaborative robots of the model FANUC CRX-25iA, one with a moving pedestal and one with a permanently placed pedestal. The movable pedestal opens for the use of the FANUC robot at other parts of the factory. The end effector of the FANUC robot has a glue gun attached to it that will disperse glue. A camera mounted on a beam in the workstation is used to scan the position of where the glue should be applied. The current workstation uses a telfer with a manual glue gun attached, by keeping this the flexibility is kept. In addition, preventative measures used in the risk assessment is added to the workstation. The authors recommend the implementation of collaborative robots for the manufacturing of the D6 and D4 cylinder heads. The findings in this thesis indicates a potential increase of production rate with 44%, with less errors and high degree of safety. Also, the ergonomic evaluation points towards that the operators will experiencing less strain compared to the current workstation. The risk assessment reveals that this solution can be implemented with acceptable levels of risks to the operators and the property of Volvo Powertrain. The implementation of collaborative robots is assessed to be economically justifiable due to the payback time being 0,6 years. The authors assess that the positive effects that apply to the D6 cylinder head will also apply to the D4 cylinder head. An implementation of the solution that the authors present would increase the knowledge at Volvo Powertrain and enable new exciting projects with collaborative robots in the future.